Sel Bahan Bakar Oksida Padat Sebagai Sumber Energi Yang Ramah Lingkungan di Masa Pandemik COVID-19 - Rihan Amila Putri; Atiek Rostika Noviyanti (Jambura Journal of Chemistry, 2021)
COVID-19 (caused by SARS-CoV-2) has spread throughout the world. The need of power supply for hospitals are one of the concerns during pandemic. Power requirement can be fulfilled by SOFC through an electrochemical process to generate electricity. SOFC efficiency up to 85% which can be an alternative that providing an environmentally friendly (low emission) and efficient to generate electricity. SOFC components which fulfilled various aspects, are expected to produce good electrochemical performance in order to form high efficiency when combined with CHP, APU, or UPS to help overcoming the electricity supply in hospitals and health centre during the COVID-19 pandemic.